THE IMPLEMENTATION OF STEM EDUCATION IN ELEMENTARY SCHOOLS: A LITERATURE REVIEW ON ITS POTENTIAL AND CHALLENGES - Sugeng (CV. Fahr Publishing, 2025)
This study aims to examine the implementation of STEM (Science, Technology, Engineering, and Mathematics) education in elementary schools, focusing on identifying potentials, barriers, and novel approaches to enhance student engagement and learning outcomes. A systematic literature review method was employed, collecting peer-reviewed journal articles, conference proceedings, and relevant reports published in the last five years (2019–2025) from databases such as Scopus, Web of Science, and ERIC. Data were analyzed using thematic synthesis, coding key elements such as teacher preparedness, student attitudes, curriculum integration, resource availability, and contextual factors, followed by the development of an integrative framework for STEM implementation. The findings indicate that teacher readiness, limited instructional materials, curriculum rigidity, and policy misalignment remain major barriers, while innovative pedagogical practices, early exposure to STEM, and student-centered approaches represent significant potentials for enhancing elementary STEM education. The study also identifies gaps in current research, particularly the lack of integrative models that link student attitudes, teacher capacity, and contextual readiness, as well as the underrepresentation of rural and under-resourced schools in STEM research. The novelty of this research lies in proposing a comprehensive, adaptable framework that combines these elements to guide effective STEM implementation in elementary classrooms, especially in diverse socio-economic settings. In conclusion, integrating teacher development, student motivation, and contextual support into STEM planning is critical to achieving sustainable and equitable outcomes, providing actionable insights for educators, policymakers, and curriculum developers globally.